2001
DOI: 10.1002/1099-0682(200105)2001:5<1227::aid-ejic1227>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Co2+ Translocation in a Terpyridine−Cyclam Ditopic Receptor

Abstract: The coordination behaviour of the ditopic receptor of 1‐[p‐(2,2′:6′,2′′‐terpyrid‐4′‐yl)tolyl]‐1,4,8,11‐tetraazacyclotetradecane (L1) towards Co2+ in acetonitrile/water (70:30, v/v) has been investigated. At acidic pH values, the L1−H+−Co2+ system shows an oxidation wave at 150 mV vs. SCE, characteristic of Co2+ in a bis(terpyridine) environment. Upon addition of OH−, a reduction in the intensity of the wave at 150 mV is observed and a new oxidation wave appears at 1.30 V. This new wave is close to that found f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 17 publications
2
53
0
Order By: Relevance
“…In preliminary studies, receptor 736 was found to serve as a selective fluorescent sensor for ATP in 7:3 acetonitrile:water at slightly acidic pH values (4-6). 746 No changes in the emission spectrum were observed upon the addition of chloride, sulfate, or inorganic phosphate. Further studies examined the dimetallic complex produced upon coordination of Cu 2+ to the cyclam unit of ligand 736 .…”
Section: Major Phosphate-binding Functionalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In preliminary studies, receptor 736 was found to serve as a selective fluorescent sensor for ATP in 7:3 acetonitrile:water at slightly acidic pH values (4-6). 746 No changes in the emission spectrum were observed upon the addition of chloride, sulfate, or inorganic phosphate. Further studies examined the dimetallic complex produced upon coordination of Cu 2+ to the cyclam unit of ligand 736 .…”
Section: Major Phosphate-binding Functionalitiesmentioning
confidence: 99%
“…Further studies examined the dimetallic complex produced upon coordination of Cu 2+ to the cyclam unit of ligand 736 . 747 For example, in acetonitrile:water (7:3), the stability constant between [ 736:Cu )] 4+ and ATP was determined to be log K = 6.10 through potentiometric titrations. CV studies supported the conclusion that non-coordinating anions (ATP, ADP, GMP, sulfate, and inorganic phosphate) interacted with the 736:Cu receptor through electrostatic (Coulombic) interactions rather than metal-anion coordination.…”
Section: Major Phosphate-binding Functionalitiesmentioning
confidence: 99%
“…Such interactions have also been used by scientists in the development of binders for anions with impressive results. [54][55][56][57][58][59][60][61][62][63][64] These sensors are composed of a fluorescent or nonfluorescent multivalent ligand, which coordinates with one or two metal cations, such as Zn 2+ , Cu 2+ , and Cd 2+ , to form a ligand-metal complex. Besides, fluorescent lanthanides, such as Tb and Eu have also been used in some sensors, especially those made by the Gunnlaugsson group.…”
Section: Metal-anion/ligand Interactionsmentioning
confidence: 99%
“…One area of application of covalent interactions involving metals is organic anion detection because a large number of biomolecules such as peptides, nucleotides, phospholipids, and carbohydrates are anionic compounds [162,163]. There have been some impressive chemosensors [162][163][164][165][166][167][168][169][170][171][172][173]. One interesting strategy is the design of sensors based on dimetallic architectures that utilize a bridging mechanism.…”
Section: Chemosensors Based On Metal-anion/ligand Interactionsmentioning
confidence: 99%
“…These receptors bind with histamine in water with high selectivity and binding constants, with the highest being 1.6 × 10 5 /M in pH 8 buffer. Finally, Manez and coworkers developed a sensor (52) using a multicomponent dinuclear system containing a Ru(Tpy) 2+ 2 fluorescent core and a cyclam-Cu 2+ complex [168]. The fluorescence of the Ru(Tpy) 2 2+ core in an aqueous environment (acetonitrile/water, 70 : 30) is quenched by the Cu 2+ cation.…”
Section: Chemosensors Based On Metal-anion/ligand Interactionsmentioning
confidence: 99%